Controle hierárquico para a equação do calor via estratégia Stackelberg-Nash - Albuquerque., Islanita Cecília Alcantara de (2011)
We have as main issue in this work the Hierarchical Control, which consists in a leader-followers system. We studied in special the heat equation approximate controllability under Stackelberg-Nash’s strategy, which is directed in controlling every system from local controls choices with the minimum possible costs.